#### Answer

$f^{-1}(x) = \sqrt[3] {2 - 5x}$

#### Work Step by Step

$f(x) = \frac{2 - x^{3}}{5}$
$5y = 2 - x^{3}$
$x^{3} = 2 - 5y$
$x = \sqrt[3] {2 - 5y}$
$f^{-1}(x) = \sqrt[3] {2 - 5x}$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

$f^{-1}(x) = \sqrt[3] {2 - 5x}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.